2021
DOI: 10.3390/genes12101577
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Infection Alters the Microbiome: Elite Athletes and Sedentary Patients Have Similar Bacterial Flora

Abstract: Regular exercise can upgrade the efficiency of the immune system and beneficially alter the composition of the gastro-intestinal microbiome. We tested the hypothesis that active athletes have a more diverse microbiome than sedentary subjects, which could provide better protection against COVID-19 during infection. Twenty active competing athletes (CA) (16 male and 4 females of the national first and second leagues), aged 24.15 ± 4.7 years, and 20 sedentary subjects (SED) (15 male and 5 females), aged 27.75 ± 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 49 publications
(56 reference statements)
0
20
0
Order By: Relevance
“…Of the 43 studies and 11 518 infected athletes included in this systematic review, the median number (IQR) of participants per study was 26 (15–101). The included studies were conducted in Argentina,15 Australia,16 Brazil,1 17 Denmark,18 Finland,19 Germany,20–23 Hungary,8 24 25 Italy,9 26–31 Poland,14 Qatar,2 Russia,32 Serbia,33 Turkey,34 UK35 36 and USA 3 6 7 37–47. One study was a multicentre collaboration led by researchers in South Africa,48 and one study was conducted across different countries in Europe 49…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 43 studies and 11 518 infected athletes included in this systematic review, the median number (IQR) of participants per study was 26 (15–101). The included studies were conducted in Argentina,15 Australia,16 Brazil,1 17 Denmark,18 Finland,19 Germany,20–23 Hungary,8 24 25 Italy,9 26–31 Poland,14 Qatar,2 Russia,32 Serbia,33 Turkey,34 UK35 36 and USA 3 6 7 37–47. One study was a multicentre collaboration led by researchers in South Africa,48 and one study was conducted across different countries in Europe 49…”
Section: Resultsmentioning
confidence: 99%
“…Eleven (25%) studies included only male athletes,2 9 15 18 19 21 22 29 33 36 49 2 (5%) studies included only female athletes32 34 and 22 (51%) studies included both male and female athletes 1 3 6 8 14 16 24–28 35 37–39 41–44 46–48. Eight (19%) studies did not report data on sex 7 17 20 23 30 31 40 45.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five articles included in our study reported that gut microbiota composition can be a predictive factor in the severity of COVID-19 disease [24,27,61,71,78], and only one study reported no such association [67]. It has been shown that normal gut microbiota can decrease the severity of the COVID-19 course [20,24,42,43]. Babszky et al reported that Bacteroidetes spp.…”
Section: Severitymentioning
confidence: 87%
“…Babszky et al reported that Bacteroidetes spp. in the feces has an anti-in ammatory effect and possess protective features against severe COVID-19 infection [43]. Similarly, Dereschuk et al reported that Less severe COVID infection can be associated with the presence of Bacillus subtilis spp.…”
Section: Severitymentioning
confidence: 98%